Intelligent web-based expert system for early diagnosis of cancer - Zakaria, Azizi; Siraj, Fadzilah; Abu Bakar, Nur Azzah (Universiti Utara Malaysia, 2006)
Cancer is one of the major health problems in Malaysia. This disease has become increasingly important as a public health concern with the development and progress that has been achieved in this country. Each year cancer affects at least nine million people world-wide and kills five million. Cancer has been reported as the fourth leading cause of death in Malaysia. The incidence of cancer in Malaysia is estimated to be around 150 per 100,000 population. This means there are about 35,000 new cancer cases each year. In the year 2000, there were 40,244 admissions for cancer in government hospitals. As the number of new cases of cancer growing every year, Malaysia is facing a serious shortage of expert oncologist. Currently, there are only 28 oncologist in Malaysia with 7 of them working in government hospitals. Furthermore, scientific studies and successful control activities have indicated that one third of all cancer cases are preventable, and a further one third are potentially curable if diagnosed sufficiently early. Unfortunately, delays in detection of cancer are common among Malaysian cancer patients. One solution to these problems is to develop a medical expert system that can replicate the expertise of an oncologist. Expert system can play an important role in assisting a doctor to manage their daily duties. It can also improve productivity and replace an expert at any location and time where expertise is not readily available. With the growing influence of World Wide Web (WWW), the expert system can be deployed on the WWW where the system is available anytime and can be easily accessed globally by large number of people. Thus, this study will explore the deployment of a web-based medical expert system that can help to diagnose and provide early detection of cancer. The system will also create the awareness and educate the public on possible preventive measures and risk involves by providing a simple and friendly questions and answers session.